The effects of macroeconomic variables to the return of Bursa Malaysia / Huraiyah Isry Ismail - Ismail, Huraiyah Isry (Faculty of Business and Management, 2012)
The main purpose of this paper is to determine the four areas of objectives which to study the relationship between Consumer Price Index, Money Supply, Interest Rate and Crude Oil Price to the return of KLCI. To answer these objectives, Multiple Linear Regression has been selected where the result can be explained by the F-Stat and P Value. The quarterly data of each index for ten (10) years will be used and collected from the Data Stream. Based on the Multiple Linear Regression, the results show that the coefficient of Consumer Price Index, Money Supply and Crude Oil Price are significant with KLCI. It means, any changes in the CPI, Money Supply and Crude Oil Price will affect the return of KLCI. However, interest rate is insignificant with KLCI which means there is no significant relationship between those 2 variables.